The Rise of AI in HR: How Artificial Intelligence is Changing the Way We Work - Wijono, Djoko; Sabardini, Sri Ekanti (Penelitian dan Pengembangan Ilmu, 2024)
The application of artificial intelligence (AI) in human resources (HR) management is an increasingly rampant trend in the contemporary work environment. This study aims to investigate the role of ethics and fairness in the use of AI systems in HR decision making, as well as their impact on employee satisfaction and well-being. The research method used is a systematic literature review which involves analysis of a number of relevant articles from international databases. The results of the discussion highlight the importance of taking into account ethical and justice aspects in the development, implementation and use of AI in HR, as well as its positive implications for employee satisfaction and well-being. The implications of this research include the importance of paying attention to ethical and justice principles in the use of AI in HR to ensure fair, transparent and accountable decisions, which in turn can increase employee satisfaction and well-being.